The DNA Barcoding of Several Commercial Fish from Simeulue Islands Coast of Aceh Using Cytochrome Oxidase Sub Unit I (COI) Gene Marker - Edwarsyah Edwarsyah; Muhammad Nasir; Muhammad Banda Selamat (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Simeulue is a cluster of islands that rich of commercial fisheries in Aceh waters. Management of the fisheries products is highly related to species identification in order to ascertain the appropriate steps to manage the resources sustainably. Identification using DNA barcoding tools is the right answer for the problem that have not been able to be resolved even by morphological approach. Some of 11 individual samples were taken from 6 sampling points based on lobster’s catchment and cultivation areas. All of the samples were identified using COI mitochodrial DNA resulting 6 species including Scomber scombus, Scomberomorus plurilineatus, Octopus cyanea, Taeniura Lymna, Sympterygia bonapartii and Panulirus versicolor. The DNA bases were aligned using MEGA application and Neigbour- Joining method, Kimura 2 parameters resulting a 690 base pairs nucleotides. Reconstruction of philogenetic tree shows that the species of Simeulue were conjoined into one clade with the sequences downloaded from genebank. It shows that those species were closely related genetically indicating by the bootstrap value of Scomber scombus (100), Scomberomorus plurilineatus (100), Octopus cyanea (100). The results of the study shows that the DNA barcoding tools can explicate not only the identification up to the species level but also the genetic relationship that can be seen from the interspecies bases composition.